Embedded Wafer Level Ball Grid Array (eWLB) Technology for Millimeter-Wave Applications - Wojnowski, Maciej; Lachner, Rudolf; Böck, Josef; Wagner, Christoph; Starzer, Florian; Sommer, Grit; Pressel, Klaus; Weigel, Robert (IEEE 13th Electronics Packaging Technology Conference (EPTC), 2011)
The embedded wafer level ball grid array (eWLB) is a novel packaging technology that shows excellent performance for millimeter-wave (mm-wave) applications. We present simulation and measurement results of single-ended and differential transmission lines realized using the thin-film redistribution layers (RDL) of an eWLB. We demonstrate the capabilities for the integration of passives on example of a configurable 17/18 GHz down-converter circuit realized in silicon-germanium (SiGe) technology with a fan-in eWLB differential inductor used for the LC tank. We compare the performance of differential chip-package-board transitions realized in an eWLB and in other common package types. We report an optimized compact chip-package-board transition in the eWLB. We obtain a simulated insertion loss as low as -0.65 dB and a return loss below -16 dB at 77 GHz without external matching networks. We introduce the concept of antenna integration in the eWLB and show examples of single-ended and differential antenna structures. Finally, we present for the first time a single-chip four-channel 77 GHz transceiver in SiGe integrated in the eWLB package together with four dipole antennas. The presented examples demonstrate that the eWLB technology is an attractive candidate for mm-wave applications including system-in-package (SiP).
elib2cris::1512001600,wojnowski2011
Keywords: Ge-Si alloys; ball grid arrays; dipole antennas; microwave integrated circuits; millimetre wave integrated circuits; radio transceivers; system-in-package; transmission lines; wafer level packaging; LC tank; SiGe; antenna integration; compact chip package board transition; differential transmission line; dipole antennas; down converter circuit; eWLB technology; embedded wafer level ball grid array; frequency 17 GHz; frequency 18 GHz; frequency 77 GHz; millimeter wave applications; single chip four channel transceiver; single ended transmission line; system-in-package; thin film redistribution layer; Attenuation; Coplanar waveguides; Dipole antennas; Inductors; Insertion loss; Transmission line measurements; Electronics packaging